Application of the pulsed light technology to mycotoxin degradation and inactivation. Issue 5 (25th October 2011) - Moreau, Morgane; Lescure, Geoffroy; Agoulon, Adrien; Svinareff, Pascal; Orange, Nicole; Feuilloley, Marc
ABSTRACT The persistence of mycotoxins and their metabolites in agricultural products is a major safety concern because of their high resistance to all kinds of decontamination techniques. In this study, we evaluated the effectiveness of the pulsed light technology for the degradation of mycotoxins. We report that eight flashes of pulsed light destroyed of 84.5 ± 1.9, 72.5 ± 1.1, 92.7 ± 0.8 and 98.1 ± 0.2% of zearalenone, deoxynivalenol, aflatoxin B1 and ochratoxin in solution. The degradation of the molecules was monitored by HPLC and LC‐MS/MS analysis. We estimated the potential toxicity of zearalenone and deoxynivelenol after exposure to a pulsed light treatment using the Caenorhabditis elegans survival tests. The genotoxicity of aflatoxin B1 was also investigated using a complete Ames test. The results show that the treatment of zearalenone and deoxynivelenol by single or multiple flashes of pulsed light is associated with a stagnation or marginal decrease of the toxicity of the mycotoxins and that treatment of aflatoxin B1 by pulsed light can completely eliminate the mutagenic potential of this mycotoxin. This work provides the first demonstration of a nonthermal technology allowing mycotoxin destruction and inactivation of their mutagenic activity. Copyright © 2011 John Wiley & Sons, Ltd.